Ta'zir Concept in Sharia Banking (Analysis of Fatwa DSN MUI Number: 17/DSN-MUI/IX/2000) - Muhammad Hanafiah; Anwar Hafidzi (Universitas Muhammadiyah Sidoarjo, 2021)
This research proves that the giving of ta'zir in the DSN MUI fatwa is based on mutual agreement which aims to obtain rights as users and depositors. The method used in this study is a literature review with a normative legal approach to the MUI DSN fatwa NUMBER: 17 / DSN-MUI / IX / 2000. this research found that ta'zir is a sanction in the form of money (a fine), the amount of which is not determined, but rather was made based on the agreement of both parties. In addition, the fine funds are not used as bank revenue but as social funds. Penalty is not to replace the value of real loss that must be experienced (fixed cost) by the bank, but so that customers are more disciplined in carrying out their obligations.